2018
DOI: 10.17951/pjss.2018.51.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture under no-tillage and tillage systems in maize long-term experiment

Abstract: 12Abstract. The aim of the study was to evaluate the impact of conventional till (CT) and no-till (NT) cultivation systems in a long-term experiment with maize on soil water dynamics using continuous soil moisture (SM) measurements in the 2014, 2015, 2016 vegetation seasons. The ability of HERMES model to simulate SM was also evaluated in Polish conditions. The long-term experiment with maize is located in the Grabów Experimental Farm of Institute of Soil Science and Plant Cultivation -State Research Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…According to Doorenbos and Pruitt (1977) and Alvarez and Steinbach (2009), the water layers available under NT can cover a loss by evapotranspiration ranging from 1 to 3 days of the crop during flowering stage, especially in dry areas with high atmospheric demands. Król et al (2018) also confirmed, in a longterm experiment on maize crop established in central Poland where the average rainfall is 436 mm that NT system increased SWC compared to CT system. Up to 60 cm depth of a loamy sand soil, SWC under NT system was greater than CT system from 6% in…”
Section: Soil Water Dynamicssupporting
confidence: 56%
“…According to Doorenbos and Pruitt (1977) and Alvarez and Steinbach (2009), the water layers available under NT can cover a loss by evapotranspiration ranging from 1 to 3 days of the crop during flowering stage, especially in dry areas with high atmospheric demands. Król et al (2018) also confirmed, in a longterm experiment on maize crop established in central Poland where the average rainfall is 436 mm that NT system increased SWC compared to CT system. Up to 60 cm depth of a loamy sand soil, SWC under NT system was greater than CT system from 6% in…”
Section: Soil Water Dynamicssupporting
confidence: 56%